Structural-semantic peculiarities of meteorological metaphor in the English and Kazakh languages - Roza M. Tayeva, Meruyert S. Ongarbayeva,; Yermakhanova, Saule B.; Kadhim, Kais Amir (Opción, 2020)
The purpose of this study is to determine the specifics of the meteorological metaphor and metaphorical processes of the lexical-semantic field wind on the material of balanced National Corpora data, sub-corpora of literary texts, and scientific texts, magazines, newspapers, and academic writing. As a result, the religious metaphor with the wind of God literally conveys the meaning of the wind from the Almighty, the wind as a blessing from the Lord, grace. In conclusion, the metaphorical conceptualization of wind in the two languages differs in how they affect other objects.